A figura do analista na clínica das anorexias e bulimias - Jacobsohn, Patricia Gipsztejn (2017)
This research aims at investigating aspects of the clinical practice of analysts who work with patients with anorexias and bulimias. It also aims at investigating the specificities and issues of particular relevance in the analyst's encounter with his/her patient; countertransference issues arising in the encounter of this analytical duo; checking if it is possible to correlate these countertransference aspects with the difficulty in attendance and bond with these patients; if there is a difficulty in these services, which mobilizes personally and which issues involved in the professional choice of these analysts to deal with this type of patient; raising personal questions of these analysts (such as history of eating disorder in their personal or family histories) and correlate this issue with professional choice; and also investigating whether the way the analyst deals with questions about his/her own body and how he conducts his/her food life influence his clinical practice. A theoretical research was carried out, with bibliographical revisions referring to the proposed theme and the concepts that are articulated to the work. Semi-open interviews were also carried out with 5 (five) female analysts who study and work with patients with anorexias and bulimias